Limited pharmaceuticalisation: a qualitative case study of physiotherapist prescribing practices in an NHS Trust in England following the expansion of non‐medical prescribing in the UK - Wilson, N; Pope, C; Roberts, L; Crouch, R (Wiley, 2019)
Over the last quarter century, non‐medical prescribing in the UK has grown significantly; eight non‐medical professional groups now have authority to prescribe a wide range of medicines, suggesting it could be a potent driver of pharmaceuticalisation. In this article, we present data from a case study of physiotherapists’ prescribing practices. UK physiotherapists have had legal rights to prescribe medicines since 2005, but relatively little is known about the contribution they make to expanding patient access to medicines. We approached our study through a lens of governmentality to capture the mentalities and micro‐practices governing physiotherapist non‐medical prescribing. Ethnographic methods were used to gather data from an outpatient orthopaedic service in an NHS Trust in England employing physiotherapist prescribers. From the data, we identified a grid of intelligibility – an organising framework formulated by powerful discourses and technologies of government through which physiotherapist prescribing was acted into being. A primary effect of this grid was the constitution of new physiotherapist subjectivities, mostly as non‐prescribers of medicines contrary to policy intentions, underpinned by a familiar and enduring template of medical professionalism.